Electrochemical properties of poly(aniline-co-N-methylthionine) for zinc-conducting polymer rechargeable batteries. (1st February 2016) - Chen, Chuanxiang; Hong, Xiaozhang; Chen, Ankang; Xu, Tingting; Lu, Lin; Lin, Shengling; Gao, Yuhua
Highlights: Poly(aniline- co - N -methylthionine) (PANMTh) is synthesized using electrochemical copolymerization. A Zn-polymer secondary battery is fabricated using PANMTh as cathode. Improved electrochemical properties of PANMTh are observed. The battery has a maximum discharge specific capacity of 146.3 A h Kg −1 . The battery shows an excellent cyclic stability. Abstract: Polyaniline is a promising electrode active material for secondary batteries because of its high conductivity, light weight, good redox reversibility and high environmental stability. However, the low attainable specific capacity of polyaniline limits its applicability in commercial battery systems. Here, we prepare a novel copolymer, poly(aniline- co - N -methylthionine) (PANMTh), by incorporating redox-active N -methylthionine unit into a polyaniline chain via electrochemical copolymerization. The resultant PANMTh film exhibits greatly enhanced electrochemical properties and cycling stability when used as a cathode active material in an aqueous Zn-polymer secondary battery. It delivers a high specific capacity of 146.3 A h kg −1 at a current density of 1 mA cm −2 and retains about 99.4% of the capacity over 150 consecutive cycles at a current density of 2 mA cm −2 .